A RHETORICAL ANALYSIS BASED ON THE SCIENCE OF MA‘ĀNĪ IN THE POETRY OF TA‘LĪM AL-MUTA‘ALLIM BY AL-ZARNŪJĪ: TAḤLĪL BALĀGHĪ QĀ’IM ‘ALĀ ‘ILM AL-MA‘ĀNĪ FĪ ASY’ARI KITĀB TA‘LĪM AL-MUTA‘ALLIM LI’L-IMĀM AL-ZARNŪJĪ - Mohammad Wijdan Faiq Fadhlillah; Yulianti; Agus Riyadi (Program Studi Bahasa dan Sastra Arab STIABI Riyadul 'Ulum, 2025)
Ta’līm al-Muta‘allim is a significant classical text widely studied by students of Islamic knowledge. It includes numerous poems used to convey educational messages, advice, and learning methodologies. However, understanding these poems often becomes challenging due to the complexity of rhetorical terms such as khabar, insya’, and qashar. This study aims to examine the rhetorical purposes of the poems in Ta’līm al-Muta‘allim, with a focus on how they function within the framework of ‘ilm al-ma‘ānī (the science of meanings) in Arabic rhetoric. Adopting a qualitative approach using library research and documentation methods, the research applies descriptive and analytical techniques to identify and classify the rhetorical features found in the text. The research identifies 57 poetic verses across several chapters, categorized as follows: khabar ibtida’i (57), khabar talabi (8), insya’i talabi (114), insya’i ghair talabi (3), qashar (15), fasl (2), wasl (9), ijaz (9), itnab (4), and musawah (1). The most dominant aspect is insya’i talabi. This research contributes to a deeper understanding of ‘ilm al-ma‘ānī in Arabic literature and serves as a foundational reference for further studies in Arabic rhetoric